A detailed study on loss processes in solar cells. (1st February 2018) - Wang, Ao; Xuan, Yimin
Abstract: Only a small part of the incident solar energy converts to the electrical power in photovoltaic devices. The majority of the energy loss contributes to the heat generation in devices and thus leads to a temperature rise, causing an inevitable impact on the performance of photovoltaic devices. Hence, loss processes in solar cells play very important roles in solar-electric conversion process. This paper systematically studies both the intrinsic and extrinsic losses in solar cells. Energy distributions of solar cells with different kinds of parameters are presented to characterize the different kinds of loss processes in detail. The sensitivities of loss processes to the structural and operating parameters of solar cells such as external radiative efficiency, solid angle of absorption and operating temperature are discussed, for the parameters have significant impact on the loss processes. The external radiative efficiency, solid angle of absorption (e.g., the concentrator photovoltaic system), series resistance and operating temperature are demonstrated to greatly affect the loss processes. Furthermore, based on the calculated thermal equilibrium states, the temperature coefficients of solar cells versus the bandgap E g are plotted. Highlights: Dominant losses and parameters of affecting the solar cell efficiency are discussed. Non-radiative recombination loss is remarkable in high-concentration-ratio solar cells. Series resistance plays a key role in limiting non-radiative recombination loss.